2006
DOI: 10.1021/jf061547l
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric Resolution and Biotoxicity of Methamidophos

Abstract: Despite the fact that the biological processes of chiral pesticides are enantioselective, the biotoxicity of methamidophos with respect to enantioselectivity has so far received limited research. In this study, the enantiomeric separation and biotoxicity of the two enantiomers of methamidophos were investigated. Successful enantioseparation of methamidophos using high-performance liquid chromatography on a Chiralcel OD column was achieved. As indicated by the optical rotation and circular dichroism detection, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 20 publications
6
85
0
Order By: Relevance
“…[5][6][7][8][12][13][14]32,33 In this investigation, satisfactory resolution of salithion enantiomers was achieved on all of the three CSPs of derivative cellulose and amylase we selected, among which the Chiralpak AD column offered the highest a of more than 1.20 suggesting a baseline resolution. 34 Moreover, the chiral recognition ability of Chiralpak AD also seems better than that of Chiralcel OB and Chiralpak OT(1), the two columns that have been used to separate salithion enantiomers previously.…”
Section: Results and Discussion Enantiomer Separation And Identificationmentioning
confidence: 89%
See 2 more Smart Citations
“…[5][6][7][8][12][13][14]32,33 In this investigation, satisfactory resolution of salithion enantiomers was achieved on all of the three CSPs of derivative cellulose and amylase we selected, among which the Chiralpak AD column offered the highest a of more than 1.20 suggesting a baseline resolution. 34 Moreover, the chiral recognition ability of Chiralpak AD also seems better than that of Chiralcel OB and Chiralpak OT(1), the two columns that have been used to separate salithion enantiomers previously.…”
Section: Results and Discussion Enantiomer Separation And Identificationmentioning
confidence: 89%
“…Recently, increasing studies have demonstrated that enantioselectivity also exists in the in vivo acute aquatic toxicity of chiral OPs. [5][6][7]9,10,[12][13][14] Salithion ((RS)-2-methoxy-4H-1,3,2 k 5 benzodioxaphosphorin 2-sulfide), an organophosphorus pesticide, which was first synthesized in 1963, is used for control of a broad spectrum of insect pests in orchards or vegetables. 15,16 In recent years, because of its high efficacy, low cost, and capacity to control pyrethrin-resistant pests, 17 salithion has been considered as an effective alternative of the highly toxic OPs in China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Studies showed that there was obvious enantioselectivity in their acute toxicity 11 and, also, inhibition of AChE activity. 12,13 The basis for the difference between stereoisomers lies in the three-dimensional nature of organic drug molecules and their target receptors, which are most often proteins. This provides a basis for the spatial recognition of stereoisomeric forms of chiral molecules and critical binding sites for drug-protein interactions.…”
Section: Introductionmentioning
confidence: 99%
“…[56][57][58] Recently, enantiomeric separation and quantification of various chiral pesticides by highperformance liquid chromatography and capillary electrophoresis have been reported by various researchers. [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] The general advantages of ICP-MS detection for chiral pesticide determinations in complex environmental samples have been reported. 76) Scientists determined the S and R isomers of metolachlor (3) in water by enantioselective enzyme immunoassay.…”
Section: Chiral Separationsmentioning
confidence: 99%